Reconsidering partnerships in education in emergencies - Menashy, Francine; Zakharia, Zeena (Education Policy Analysis Archives, 2022)
International actors increasingly advocate for partnerships in education in emergencies (EiE) to address the dire educational opportunities of school-aged children in sites of disaster, armed conflict, forced migration, and other humanitarian crises. This study explores the nature of partnerships in EiE. We examine the impetus behind an expansion of partnerships among diverse global actors and key characteristics, relationships, and dynamics within these partnerships. Using data collected from key informant interviews and documents from organizations involved in the Syria refugee education response (2018-2021), we detail two emerging characteristics of partnerships in EiE: (1) market-based principles in rhetoric and practice; and (2) a rise in private sector participation. While partnerships aim to improve coordination between agencies, our study uncovers the counterintuitive finding that competition characterizes the EiE partnership space more often than coordination. Furthermore, despite the education and humanitarian community’s promotion of a “localization agenda”—prioritizing full participation of affected local communities as partners in education policy and implementation—our research points to a maintained hierarchy where international actors hold most influence in EiE. We discuss the practical implications of this power asymmetry within the broader context of marketized humanitarianism, and raise concerns regarding equity within unchecked partnerships.